Boosting the Activity of Ligand‐on Atomically Precise Pd3Cl Cluster Catalyst by Metal‐Support Interaction from Kinetic and Thermodynamic Aspects. Issue 24 (22nd August 2018) - Yun, Yapei; Sheng, Hongting; Yu, Jie; Bao, Linquan; Du, Yuanxin; Xu, Fengqing; Yu, Haizhu; Li, Peng; Zhu, Manzhou
Abstract: Atomically precise nanoclusters (APNCs), as ideal model catalysts, revealed great advantages to deep‐understand of reaction mechanisms in heterogeneous catalysis. Boosting the activity of APNCs is the most critical issue under the premise of maintaining structure invariance. Herein, utilizing Metal‐Support Interaction (MSI) strategy, we prepared an excellent and recyclable catalyst for aerobic oxidation by combination of an otherwise inert nanocluster [Pd3 Cl(PPh2 )2 (PPh3 )3 ] + [SbF6 ] − (denoted as Pd3 Cl) with functional titanate nanotubes (TNT). The promising Pd3 Cl/TNT composite gives rise to excellent conversion with 100% selectivity without any additives at 30 °C under an oxygen pressure. This result is unprecedented in ligand‐on nanocluster catalysts without high temperature calcination. The distinct difference between their activities of Pd3 Cl/TNT composite and fresh Pd3 Cl nanocluster is explained by the presence of the MSI effect, as confirmed using X‐ray photoelectron spectroscopy (XPS) analysis. Theoretical simulations are further carried out to elucidate the catalytic mechanism, indicating the MSI effect promotes the crucial β‐H elimination step in both kinetic and thermodynamic aspects. This work presents the example of atomic‐level understanding of the effect of MSI on facilitating the APNCs catalytic properties. Abstract :